Lunch hour - Kerr, Jean (Collins) (Doubleday, 1981)
This comedic play covers the vagaries of marital bliss, once the honeymoon is over. The characters include Oliver DeVreck, a psychiatrist who needs more help than any of his patients, and Carrie Sachs, a patient of Oliver's whose husband is having an affair with Oliver's wife.